Anti-Easter Story by Ivan Bunin “Mowers” (structure, system of Images, “Russian Idea”) - O. V. Bogdanova; Minjie Liu (Научный диалог, 2022)
A new interpretation of I. Bunin’s story “Mowers” (1921) is proposed. If Bunin’s traditionally “short” story is considered by researchers as a realization of the theme of the Motherland, love for the lost paradise on Earth, admiration and glorification of the Russian people, the work reveals other, essentially opposite intentions of Bunin’s text. It is shown that summing up the results of the first year of emigration formed complex and contradictory thoughts about Russia and its people in Bunin’s mind. It is shown that while recreating in the story what seems to be an uncomplicated memory of the meeting with the mowers and expressing delight over their heart-wrenching song, in fact Bunin is building a complex multi-tiered narrative system. It is noted that in this system, the outer layer of the narrative (a long-standing meeting with the mowers) is crowded by today’s reflection of exiled emigrants (Paris, 1921) and is symbolized by folklore ideas about fairy-tale Russia and its primitive mythology. It is proved that the intention of the author-narrator is focused not on admiration for the past and the lost (traditional perspective), but on antagonism and rejection of the old fairy tale, which, according to Bunin of the 1920s, has come to an end. The central motives of the story are rethought, the semantic recoding of the title image of the mowers is traced.